2015
DOI: 10.1021/acssuschemeng.5b00896
|View full text |Cite
|
Sign up to set email alerts
|

Green and Sustainable Tandem Catalytic Approach for Fine-Chemicals Synthesis Using Octahedral MnO2 Molecular Sieve: Catalytic Activity versus Method of Catalyst Synthesis

Abstract: Octahedral MnO 2 molecular sieve (OMS) was prepared using hydrothermal synthesis route in the absence and in the presence of urea. OMS was also prepared by solvent free method.Catalysts were characterized by the complementary combination of X-ray diffraction, N 2adsorption, scanning electron microscope, UV-visible spectroscopy, thermo gravimetric analysis, and NH 3 & CO 2 temperature programmed desorption techniques. Catalysts were investigated in the oxidation of benzyl alcohols, hydration of aromatic/heteroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 51 publications
(89 reference statements)
1
26
0
Order By: Relevance
“…One of the promising candidates, MnO2, has attracted a lot of research attentions, due to a large theoretical capacity of 1232 mAh/g, relatively low thermodynamic equilibrium voltage and electromotive force [4] as well as rich resources on earth and environmental friendliness [5][6][7][8][9][10]. In these several decades, a wide range of MnO2 materials with different crystallographic structures are prepared in the literature including α, β, γ and δ phases which are classified on the basis of MnO6 octahedral building blocks [11]. However, most of the transition metal oxides including MnO2 have the following problems including: (1) large volume expansion and contraction during charge and discharge processes resulting in pulverization of the particles as well as electrode films [12,13] and (2) intrinsically low electrical and ionic conductivity [14], both of which lead to unsatisfactory performances.…”
Section: Introductionmentioning
confidence: 99%
“…One of the promising candidates, MnO2, has attracted a lot of research attentions, due to a large theoretical capacity of 1232 mAh/g, relatively low thermodynamic equilibrium voltage and electromotive force [4] as well as rich resources on earth and environmental friendliness [5][6][7][8][9][10]. In these several decades, a wide range of MnO2 materials with different crystallographic structures are prepared in the literature including α, β, γ and δ phases which are classified on the basis of MnO6 octahedral building blocks [11]. However, most of the transition metal oxides including MnO2 have the following problems including: (1) large volume expansion and contraction during charge and discharge processes resulting in pulverization of the particles as well as electrode films [12,13] and (2) intrinsically low electrical and ionic conductivity [14], both of which lead to unsatisfactory performances.…”
Section: Introductionmentioning
confidence: 99%
“…Conveniently, tandem/domino processes could be triggered the introduction of an electrophilic carbonyl function. Multicatalytic processes based on an oxidation as the first step involved for example a Cu-TEMPO/peptide catalysis, [10] a Pd NPs-catalysed oxidation/supported amine-catalysed aldolisation, [11] TPAP/NMO-catalysed oxidation/prolinol derivative-catalysed conjugated addition, oxidation/Knoevenagel condensation catalysed by octahedral MnO2 molecular sieve, [12] or oxidation/Biginelli condensation in mechanochemical conditions, [13] for example. Recently, the one-pot synthesis of flavones was proposed catalysed by Au NPs supported on LDH (Layered Double Hydroxide) for which transient alcohols formed upon an aldol reaction were oxidised and further cyclised.…”
mentioning
confidence: 99%
“…Acetophenone is a common substrate in the investigation for the oxidation/aldol condensation tandem reaction. To our delight, excellent conversion and a high 88.9% isolated yield of the corresponding chalcone could be obtained under the present catalytic system (Table , entry 12), higher than MnO 2 molecular sieve . In contrast to dione, cyclohexanone and cycloheptanone gave excellent yield of the condensation products (Table , entries 13 and 14), further elucidating the existence of the steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…Urea TiN nanoparticle was found to be active catalyst only in the reaction between benzyl alcohol and acetophenone . In the same reaction, octahedral MnO 2 could give a high 92.3% conversion of benzyl alcohol with a 84.9% selectivity of E‐chalcone . Recently, Zhang et al, have found that CeO 2 could accelerate the oxidative C–C coupling of ketones and primary alcohols to produce α, β ‐unsaturated ketones without base additives .…”
Section: Introductionmentioning
confidence: 99%